Martin Luther, German saviour : German evangelical theological factions and the interpretation of Luther, 1917-1933 - Stayer, James M. (McGill-Queen's studies in the history of religion., 2000)
"Theological trend-setters in Germany after World War I were dogmatic or systematic theologians. Whether men of the right like Karl Holl or men of the left like Karl Barth, they wanted to return to Luther's fundamental Reformation theology and to justification through faith alone. In the mid-1920s, however, Barth saw the dangers posed by Lutheran theocentrism wedded to German nationalism and moved towards a more Reformed Christology and a greater critical distance from Luther. The other six major Weimar-era theologians discussed - Karl Holl, Friedrich Gogarten, Werner Elert, Paul Althaus, Emanuel Hirsch, and Erich Vogelsand - connected their theology to their Luther studies and to their hopes for the rebirth of Germany after the humiliation of the Treaty of Versailles."--Jacket